Morbilidad de los recién nacidos con síndrome de aspiración de meconio en Unidad de Cuidados Neonatales - Moreno Paladines, Richard Eduardo (2015)
The meconial aspiration syndrome (SAM) is a condition seen in term neonates that require ventilatory support, intrauterine stress cause evacuation intra-utero of meconium into the amniotic fluid which is aspired iby the fetus intra-uterus or by the newborn. Causing high rate of morbi-mortality, due to the magnitude of the problem I consider a work of investigation, the general comment was to determine the causes of morbi-mortality in neonates with meconial aspiration syndrome admitted in the Neonatology Service of the General Hospital Isidro Ayora, we realized an observational study, descriptive, analytical and that was was analyzed all the medical histories of newborns admitted to neonatal Hospital General Isidro Ayora with a diagnosis of SAM, in which a sample was selected intentional non-probabilistic, assessed 51 newly live births that presented with meconial aspiration syndrome. The results showed that the maternal causes that were attributed to the development of the syndrome Suction meconium in the newborns were: the prolonged labor 33.3 %; The Syndrome Meconium aspiration was presented in a 18 %, of the newborns and is more frequently observed in the female 56 %, and with the lowest percentage in the male 44 %, the main complication of newborns with SAM Pneumonia is intra-uterus in a 44% and asphyxiation initial moderate 22 %; it is not showed no case of mortality in the newborn meconium aspiration and 45% of the newborns with meconium aspiration syndrome that were termino newborns. KEY WORDS: Meconium aspiration syndrome, morbidity, mortality.